Exploring Emotion Regulation Strategies among Jakarta High School Students: A Qualitative Study of Cognitive Reappraisal and Expressive Suppression - Dustin Liu; Sean Natanael Wattimena; Chyarashalom Abigail P; Meiske Y. Suparman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Adolescence is a developmental period characterized by emotional instability, academic pressure, social challenges, and identity exploration. Difficulties in regulating emotions may negatively affect adolescents’ psychological well-being, interpersonal relationships, and daily functioning. This study aims to explore adolescents’ emotional experiences and emotion regulation strategies through Focus Group Discussion (FGD). The study employed a qualitative research design using thematic analysis. Participants consisted of high school students aged 17–18 years selected using purposive sampling. Data were collected through semi-structured FGDs based on Gross’s emotion regulation theory, particularly cognitive reappraisal and expressive suppression. The findings revealed that adolescents experience various emotional challenges related to academic stress, family relationships, peer interactions, and concerns about the future. The dominant emotion regulation strategy identified was expressive suppression, where adolescents tended to hide or suppress emotions due to fear of judgment and conflict avoidance. However, several participants also demonstrated cognitive reappraisal strategies by reinterpreting negative situations positively and viewing problems as opportunities for self-growth. The study also found that social support from family, friends, and schools plays an important role in helping adolescents regulate emotions more adaptively. These findings highlight the importance of emotional education programs and supportive environments to improve adolescents’ emotional well-being.